Implementation of the Treasure Hunt Learning Model in Mathematics Subjects - Hiyum, Ervinia Risti Waning; Bakhtiar, Afakhrul Masub (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2024)
Mathematics is a subject that must be studied from elementary to upper level. 85% of Mathematics teachers only use learning in the classroom and do not use innovation in learning. Therefore, this research was conducted involving 22 students from class IV of Mantup 1 State Elementary School, consisting of 11 girls and 9 boys, with the aim of creating innovation in Mathematics learning that can increase students' interest and collaboration in multiplying decimal numbers. using the Treasure Hunt model. Data was collected in two research cycles through the use of questionnaires, notes and student observation sheets. According to the data analysis carried out, the Treasure Hunt method seems to have helped students learn multiplication and division of decimals. Only 15% of students in the low category completed collaborative tasks before the intervention. The results of this research are that learning mathematics can not only be done indoors, but can be done outdoors, such as using the Treasure Hunt learning model. The use of the Treasury Hunt learning model in Mathematics subjects involves all aspects of teacher activities, student participation, and student learning activities. So with the Treasure Hunt learning model, students are more motivated and learn new things. Keywords: Mathematics, interest in learning, collaborative, Treasure Hunt.